Outcome following treatment of diaphyseal femoral osteomyelitis using a monolateral external fixation system - Mohd Yusof, Nazri; Sulong, Ahmad Fadzli (Association of study & Application of methods of Ilizarov (ASAMI-BR) & International Limb Lengthening & Reconstruction Society (ILLRS), 2017)
Background: The traditional monolateral fixation is not strong enough to overcome the strong deforming force of the strong adductor muscles which lead to varus deformity. The ring fixation, although provide a stable fixation of bone, is bulky and uncomfortable for the patients. This paper presents our result of treating patients with femoral osteomyelitis treated with a modern unilateral external fixation device. Methods: This was a prospective study of 22 consecutive patients treated for femoral osteomyelitis from 2010 till 2014. Only patients with minimal 2 years follow up were included in the study. The mean age of the patients was 28.7 (range 13 to 71) years old. Patients with osteomyelitis were divided into 3 types. type I is haematogenous osteomyelitis with pathological fracture (4 patients); type II is infected open fracture (3 patients) and type III is implant related infection (15 patients). Patients with type I osteomyelitis is treated initially with incision and drainage, and skeletal traction. External fixation is inserted after 2 to 3 weeks when the thigh swelling has reduced. In patients with type II osteomyelitis, the fracture end is resected until healthy bone. In type III osteomyelitis, the implants (2 intramedullary nails and 13 plates) are removed during the initial debridement. In 18 cases, acute compression was done after resection. In 4 cases, bone transport was done to fill the defect after the infection has been controlled. Results: Infections were resolved in all patients. All except one achieve union with mean union time of 8.5 (range 4-30) months. The mean limb length discrepancy is 2.2 cm (range 0-6 cm). Six patients (27%) have refracture following removal of the external fixation. One refracture because of persistence infection at the docking site. Three refracture at the docking site; one underwent interlocking nail, one reinsertion of LRS and one refuse further intervention. One patient had refracture at the thin bone segment. The fracture end was allowed to be overlap to get a bigger bone diameter and he was treated with reinsertion of external fixation and lengthening. One adolescent patient had fracture at the screw site was treated with skin traction. Conclusions: Monolateral external fixator is an effective alternative for stabilisation and reconstruction of femoral osteomyelitis. Caution should be taken when removing the frame to reduce the incidence of refracture. Acknowledgements: We do not have any conflict of interest in this study.